2020
DOI: 10.3390/nu12051286
|View full text |Cite
|
Sign up to set email alerts
|

Child Overweight or Obesity Is Associated with Modifiable and Geographic Factors in Vietnam: Implications for Program Design and Targeting

Abstract: Child overweight or obesity is increasing in most countries, including Vietnam. We sought to elucidate the drivers of child overweight or obesity in Vietnam and understand how they vary geographically. We compiled nationally representative cross-sectional data from the Vietnam Nutrition Surveillance Survey collected annually between 2012–2015 and household income data from the General Statistics Office. We used a quasi-Poisson log link function to calculate relative risks (RRs) of under-five child overweight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Our findings match with those reported by Arruda et al [52], who reported a greater proportion of excess weight among children from families with more favourable living environments (e.g., greater per capita income). Similarly, Beal et al [20] have recently found that higher per capita income was linked to a greater prevalence of childhood excess weight in Vietnam. Thus, income inequality could affect childhood obesity, through an increase in excessive food intake, as well as in a more sedentary lifestyle which could favour the development of overweight/obesity [1,53,54].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our findings match with those reported by Arruda et al [52], who reported a greater proportion of excess weight among children from families with more favourable living environments (e.g., greater per capita income). Similarly, Beal et al [20] have recently found that higher per capita income was linked to a greater prevalence of childhood excess weight in Vietnam. Thus, income inequality could affect childhood obesity, through an increase in excessive food intake, as well as in a more sedentary lifestyle which could favour the development of overweight/obesity [1,53,54].…”
Section: Discussionmentioning
confidence: 80%
“…For these reasons, evaluation accompanied by other body composition variables is highly recommended, such as waist-to-height ratio (WHtR), waist circumference (WC), or skinfolds in order to effectively determine the risk in participants [15]. Following this line, some studies have been conducted in order to assess the association between weight status (assessed by BMI) and socio-demographic factors, such as sex [16], type of schooling [17], area of residence [18], immigrant status [19], or per capita income [20]. For example, children from public schools have been associated with a higher prevalence of overweight or obesity [17], as well as children belonging to an immigrant family [21].…”
Section: Introductionmentioning
confidence: 99%
“…Sample selection: Studied subjects were selected randomly with similarities in age, gender, and study location. The estimated obesity rate is 5% [3]. We clinically examined 6000 children from 30 kindergartens of 4 districts in Hanoi until 234 obese children and 234 normal children were selected.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…The percentage of obese children under the age of five increased from 4.9% to 5.6% in the world [2]. This percentage has doubled in Southeast Asia from 3.2% to 7.5%, and in Vietnam from 2.6% to 5.9% [3]. ECC is one or more damage of the tooth due to tooth decay, or tooth loss due to decay or filled cavities using fillings on any milk tooth in babies between birth and 71 months of age [4].…”
Section: Introductionmentioning
confidence: 99%
“…The same report estimated that, although only about 2% of Vietnamese children and adolescents (aged five to 19) were overweight or obese in 2000 [19], by the year 2016, the prevalence of overweight and obesity had increased dramatically, with the prevalence for boys (15%) being much higher than for girls (9%) [19]. This increased prevalence of overweight and obesity in Vietnamese children and adolescents is especially concerning because the associated risk of other diet-related NCDs is subsequently higher in later life stages [15,20,21]. Furthermore, the incidence of diabetes is growing at alarming rates and has almost doubled from 3.7% in 2004 to 6% in 2016 [22,23].…”
Section: Introductionmentioning
confidence: 99%